Synthesis of NiFe2O4/SiO2/NiO Magnetic and Application for the Photocatalytic Degradation of Methyl Orange Dye under UV Irradiation - Poedji Loekitowati Hariani; Muhammad Said; Addy Rachmat; Salni Salni; Nabila Aprianti; Anisa Fitri Amatullah (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
NiFe2O4/SiO2/NiO magnetic was successfully synthesized using NiFe2O4, SiO2, and NiO as the core, interlayer, and shell, respectively. NiFe2O4/SiO2/NiO under UV light irradiation was used for photocatalytic degradation of methyl orange dye with different pH, catalyst dose, and initial dye concentration. This composite was characterized by X-ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR), Scanning Electron Microscopy-Electron Dispersive X-ray Spectroscopy (SEM-EDs), Vibrating Sample Magnetometer (VSM), UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS), and Point of Zero Charge (pHpzc). The results showed that the composite is a superparamagnetic material with a saturation magnetization value of 44.13 emu/g. It also has a band gap of 2.67 eV with a pHpzc of 6.33. The optimum conditions for photocatalytic degradation were at pH of 4; 0.50 g/L catalyst dose, and 10 mg/L initial concentration. NiFe2O4/SiO2/NiO degradation efficiency to methyl orange dye was 95.76%. The photocatalytic degradation in different concentrations follows the pseudo-first-order, where the greater the concentration, the smaller the constant rate (k). After five cycles of repeated usage, NiFe2O4/SiO2/NiO has good catalytic performance as well as efficient and favourable of a recyclable photocatalyst. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).